Evaluation of water impact for symmetric wedge by experimental and numerical methods - Nikfarjam, M.; Koto, Jaswar; Yaakob, Omar; Seif, Mohammad Saeed; Aref, A. (Zielona Góra: Uniwersytet Zielonogórski)
Evaluation of impact loads when a ship hull contacts the wave surface is one of the main issues for researchers who are going to design the structure of marine vehicles. In this paper, the results of experimental tests and numerical modeling of the distribution of pressure on different wedge-shaped models are reported and the effect of related parameters such as the deadrise angles, the weight and drop heights, is assessed.
Keywords: symmetric wedge; hydrodynamic impact; impact pressure